Internal vs external migration in post-Soviet space - Zuzanna Brunarska; Joanna Nestorowicz; Stefan Markowski (University of Warsaw, Centre of Migration Research (CMR), 2014)
The paper addresses the distinctiveness of migration flows in the post-Soviet space east of the European Union: the Commonwealth of Independent States (CIS) and Georgia. Population mobility within this region is hypothesized to differ from extra-regional population movements due to the common institutional past of these states, all of which were once the USSR republics. Within the framework of the migration systems theory, the paper offers a quantitative analysis of the scale and mechanics of cross-border population mobility in the region. By means of island analysis, it examines the intensity and distinctiveness of intra-regional migration flows relative to those between the region and third countries. Next, an econometric gravity model has been applied to identify the main drivers of migration flows in the region. The resultant findings show that the distinctiveness of the intra-regional migration processes is questionable or at best rather weak as mobility of people from and to the CIS region is relatively high. Thus, it is argued that the existence of the 'post-Soviet migration system' should not be treated axiomatically. The region is increasingly integrated into the international division of labour through trade and capital mobility and the cross-border mobility of people also reflects this globalization trend.
Keywords: 330; migration; CIS; post-Soviet space; Pajek; island analysis; gravity model; migration system